Slavery behind the wall : an archaeology of a Cuban coffee plantation - Singleton, Theresa A. (Cultural heritage studies., 2015)
In this book, Theresa Singleton examines the rarely studied slave society of Cuba, focusing on the Santa Ana de Biajacas site.